Effect of host density on life table statistics of Bracon hebetor Say, 1836 (Hymenoptera: Braconidae). Issue 1 (2nd January 2016) - Singh, Deepak; Singh, Raghvendra P.; Tripathi, C.P.M.
Abstract : Bracon hebetor Say shows high fecundity and natural rate of increase which makes it a promising enemy against Corcyra cephalonica, a very common stored grain pest. The functional response of the parasitoid can determine potential of a species to act as a biocontrol agent; it defines parasitoid's searching efficiency and provides an understanding of host–parasitoid interaction. The mean longevity of female parasitoids had no significant difference when maintained at different densities of host insects. However, progeny sex ratio was significantly affected when different host densities were maintained during its adult life. The net fecundity rate ( R 0 ) and total fecundity rate ( R t ) were highest when host density was five hosts per reproductive chamber. The mean length of generation time (T.c.) was higher on host density one compared to other densities. The intrinsic rate of increase ( r m ) was highest when the host density was five and lowest on 20 hosts per reproductive chamber. Other life table parameters were also affected significantly. On the basis of life table statistics, we can say that this type of density-responsive behaviour can be considered to be the most stabilizing one.